Akt‐dependent and Akt‐independent pathways are involved in protein synthesis activation during reloading of disused soleus muscle. Issue 3 (6th August 2016) - Mirzoev, Timur M.; Tyganov, Sergey A.; Shenkman, Boris S.
ABSTRACT: Introduction : The purpose of our study was to assess the contribution of insulin growth factor‐1–dependent and phosphatidic acid‐dependent signaling pathways to activation of protein synthesis (PS) in rat soleus muscle during early recovery from unloading. Methods : Wistar rats were divided into: Control, 14HS [14‐day hindlimb suspension (HS)], 3R+placebo (3‐day reloading + saline administration), 3R+Wort (3‐day reloading + wortmannin administration), 3R+But (3‐day reloading + 1‐butanol administration). SUnSET and Western blot analyses were used in this study. Results : Wortmannin and 1‐butanol induced a decrease in protein kinase B (phospho‐Akt) and the rate of PS ( P < 0.05) versus Control. In 3R+placebo and 3R+Wort, phosphorylation of glycogen synthase kinase 3 beta (phospho‐GSK‐3β) was increased versus Control ( P < 0.05). Wortmannin administration during reloading did not alter phospho‐p70S6K (70 kDa ribosomal protein S6 kinase) versus 3R+placebo. In 3R+But, there was a decline in phospho‐GSK‐3β versus 3R+placebo and Control. In 3R+But, there was a decrease in phopho‐p70S6K ( P < 0.05) versus 3R+placebo. Conclusions : These results suggest that PS activation during 3‐day reloading following 14HS involves both Akt‐dependent and Akt‐independent pathways. Muscle Nerve 55 : 393–399, 2017